2020
DOI: 10.1108/ajim-11-2019-0313
|View full text |Cite
|
Sign up to set email alerts
|

Social media in government offices: usage and strategies

Abstract: PurposeThe current study seeks to present and examine the strategies, management and dissemination of information on social media platforms by Israeli government organizations and agencies.Design/methodology/approachThe article uses the “Case Study” approach, through semi-structured, in-depth interviews conducted with directors in charge of the use of social media in government departments.FindingsThe findings indicate that government agencies tend to favor Facebook over other social network platforms, in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
3
17
0
2
Order By: Relevance
“…Our findings indicate that most of the links lead to internal content from within Facebook (other posts and pages). This finding is, however, in line with the identified pattern as described by Yavetz and Aharony (2020) of digital media directors' tendency to promote and prioritize content that originates from Facebook pages, sometimes at the expense of official websites. This also highlights Hofmann's et al (2013) previous findings, which suggested that adding a link to external websites leads to more negative comments than do posts without them.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings indicate that most of the links lead to internal content from within Facebook (other posts and pages). This finding is, however, in line with the identified pattern as described by Yavetz and Aharony (2020) of digital media directors' tendency to promote and prioritize content that originates from Facebook pages, sometimes at the expense of official websites. This also highlights Hofmann's et al (2013) previous findings, which suggested that adding a link to external websites leads to more negative comments than do posts without them.…”
Section: Discussionsupporting
confidence: 83%
“…This aspect is even more critical when we look into a highly diverse society like Israel, where it was found that the probability of using e-government services is much lower for non-speaking Hebrew minority groups and residents of small localities (Rosenberg, 2019). Despite these issues regarding the Israeli national portal for e-government, Israel has made substantial progress in developing strategies for governmental social media (Yavetz and Aharony, 2020). Israel's ministries and government authorities have fully implemented social media in their work plans and strategies, as they mostly prefer Facebook as their primary tool for communication and citizenry dialogue (Yavetz and Aharony, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, most contributions in the literature have developed frameworks to analyze governments' activity on social media platforms or measured their activity on Facebook more particularly (Guillamón et al, 2016). This results mainly from the fact that studies have been conducted in North America and Western Europe, where a vast majority of governments are active on at least one social media platform (Facebook initially) 1 , and most often on more (Yavetz & Aharony, 2020). At the local level, North American and European cities are increasingly present on these platforms to improve their communication with the public.…”
Section: Introductionmentioning
confidence: 99%